Towards e-learning 2.0: case study of an e-learning environment - Queirós, Ricardo (2014)
In these days the learning experience is no longer confined within the four walls of a classroom. Computers and primarily the internet have broadened this horizon by creating a way of delivering education that is known as e-learning. In the meantime, the internet, or more precisely, the Web is heading towards a new paradigm where the user is no longer just a consumer of information and becomes an active part in the communication. This two-way channel where the user takes the role of the producer of content triggered the appearance of new types of services such as Social Networks, Blogs and Wikis. To seize this second generation of communities and services, educational vendors are willing to develop e-learning systems focused on the new and emergent users needs. This paper describes the analysis and specification of an e-learning environment at our School (ESEIG) towards this new Web generation, called PEACE – Project for ESEIG Academic Environment. This new model relies on the integration of several services controlled by teachers and students such as social networks, repositories libraries, e-portfolios and e-conference sytems, intelligent tutors, recommendation systems, automatic evaluators, virtual classrooms and 3D avatars.